The trend of changes in disease severity of different foliar diseases of tomato under Gangetic alluvial plains of West Bengal - Kamei, Adam; Subrata Dutta, Suraj Goldar; Pratim Ghosh, Partha; Barman, Ashis Roy; Ray, Sujit Kumar (Indian Journal of Plant Protection, 2021)
Cultivation of tomato, an important vegetable crop of the Gangetic alluvial region of West Bengal, suffers great loss due to the occurrence of various diseases, some of which were reported to be minor in nature. In order to obtain a clear idea of the influence of changing weather parameters on tomato diseases, retrospective and real-time site-specific investigation of foliar disease scenario of tomato was initiated in the Gangetic alluvial plains of West Bengal in terms of changing trends of disease dynamics and to elucidate the major weather parameters influencing such changes. Past data and present study indicated that increasing dynamics of incidence of tomato leaf curl and target leaf spot of tomato. Target leaf spot has now been emerging as major disease during rabi tomato cultivation. The morning relative humidity in the month of January and December, irrespective of the year of observation, was positively correlated to the disease incidence pattern of the early blight disease. Maximum temperature of December and January, irrespective of the year of observations, negatively influenced leaf curl and target leaf spot disease, respectively. Further, total rainfall and average maximum temperature in January of all the observed years were identified as the important determinants of the temporal difference between disease initiation and attaining peak severity of tomato leaf curl disease. The changing trends of dynamics of various foliar diseases of tomato corresponding to the changes in weather variables under the Gangetic alluvial region of West Bengal was highlighted in the present investigation.